2011
DOI: 10.1590/s0103-50532011000700016
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the concentration of phenolic compounds in cachaça during aging in an oak (Quercus sp.) barrel

Abstract: A cachaça, tradicional e popular bebida brasileira, é obtida por meio da destilação do mosto fermentado de cana de açúcar. Dentre as etapas do processo de produção da bebida, o envelhecimento natural consiste em armazená-la em recipientes de madeira apropriados por um tempo determinado, onde ocorrem alterações na composição química, aroma, sabor e cor da bebida. Este trabalho teve como objetivo realizar um acompanhamento da composição fenólica em diferentes períodos de envelhecimento da cachaça em tonel de car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
39
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 8 publications
10
39
0
6
Order By: Relevance
“…Benzoic acid, gallic acid and syringaldehyde were the main low molecular mass compounds in the analysed samples. The results are in agreement with those previously obtained by dos Anjos et al (32) in a study about cachaça. The concentration of minor compounds such as vanillin, syringic and ferulic acids was signifi cantly higher in distillates aged in Quercus robur from Galicia.…”
Section: Concentration Of Phenolic Compounds In Grape Marc Distillatesupporting
confidence: 93%
See 1 more Smart Citation
“…Benzoic acid, gallic acid and syringaldehyde were the main low molecular mass compounds in the analysed samples. The results are in agreement with those previously obtained by dos Anjos et al (32) in a study about cachaça. The concentration of minor compounds such as vanillin, syringic and ferulic acids was signifi cantly higher in distillates aged in Quercus robur from Galicia.…”
Section: Concentration Of Phenolic Compounds In Grape Marc Distillatesupporting
confidence: 93%
“…is the estimation of the standard deviation of the regression line, and m is the slope of the calibration curve (32). The LOD and LOQ were low for all determined phenolic compounds (Table 3).…”
Section: Analytical Limits Of Detection and Quantifi Cationmentioning
confidence: 99%
“…Anjos et al (2011) [8], researched "cachaça" samples aged in oak barrels and showed that syringaldehyde and gallic acid were the compounds that showed higher concentration, results that corroborate with those found in this work.…”
Section: Quantification Of Phenolic Compoundssupporting
confidence: 85%
“…The methodology used for analysis of phenolic compounds in "cachaça" samples stored in different types of wooden barrels was described by Anjos et al (2011). The standard stock solutions were prepared at a concentration of 1000 mg/L in 40% ethanol at the following concentrations: gallic acid (6.80 mg/L), catechin (11.61 mg/L), vanillic acid (6.73 mg/L), phenol (3.76 mg/L), syringic acid (7.93 mg/L), vanillic acid (6.08 mg/L), syringaldehyde (7.29 mg/L), p-coumaric acid (6.56 mg/L), sinapic acid (8.97 mg/L), coumarin (5.85 mg/L), 4-methylumbelliferone (7.05 mg/L) and o-coumaric acid (6.56 mg/L).…”
Section: Quantification Of Phenolic Compoundsmentioning
confidence: 99%
“…Phenolic compounds were analyzed using a modifi ed method described by dos Anjos et al (27) on an Agilent 1260 Infi nity Binary LC system (Agilent Technologies, Palo Alto, CA, USA), consisting of a binary pump, a vacuum degasser, an autosampler, a thermostated column compartment and a diode array detector (DAD) with a 10-mm max-light fl ow cell. The samples were fi ltered through 0.45 μm PES (polyethersulfone) membrane fi lters (Sigma-Aldrich, Saint Louis, MO, USA) before injection, and separations were performed using an Agilent-Zorbax Eclipse XDB-C18 (4.6 mm×250 mm, 5 μm) column connected to an Agilent-Zorbax Eclipse XDB-C18 4-Pack (4.6 mm× 12.5 mm, 5 μm) pre-column.…”
Section: Hplc-dad Analysis Of Phenolic Compoundsmentioning
confidence: 99%